The frequent variant A57F in the GNE gene in patients from Russia has Finno-Ugric Mari origin - Subbotin, Dmitrii; Ionova, Sofya; Marakhonov, Andrey; Saifullina, Elena; Borovikov, Artem; Akhmadeeva, Leila; Chausova, Polina; Ryzhkova, Oksana; Zinchenko, Rena; Kutsev, Sergey; Murtazina, Aysylu (Frontiers in Genetics, 2024)
IntroductionGNE-myopathy is a distal myopathy with adult-onset and initial involvement of anterior leg compartment. A founder effect has been demonstrated for some patients from several large cohorts in different countries.MethodsIn this study, we investigated the allele frequency of the c.169_170delinsTT (p.(Ala57Phe)) variant in the GNE gene (NM_001128227.3) among different ethnic populations (Mari, Tatar, and Bashkir) and estimated the age of the mutation’s spread event.ResultsThe c.169_170delinsTT variant in the GNE gene was detected in the Mari population with an allele frequency of 0.003788 but was not found in the Tatar or Bashkir populations. The disease incidence is estimated to be 1.43 (95% CI: 0.00092–43.78) per 100,000 in the Mari population. According to our study, the estimated age of the mutation’s spread is 160.46 years (95% CI: 45.55–244.14).DiscussionBy comparing the information gathered with historical data on migration patterns in the Middle Volga region and estimating the age of the variant’s dissemination, we propose hypotheses regarding its origin and the pathways through which it spread. In the current context of increased rate of interethnic marriages, investigating the spread of common pathogenic variants from historically isolated populations is important for molecular genetic diagnosis. This approach aids in optimizing diagnostic processes and reducing the diagnostic odyssey for patients.